Learner identity in second language education - Sardar M. Anwaruddin, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
The article reports on a small-scale classroom research study conducted at a university in Bangladesh. The study is based on the argument that a theory of identity is necessary to understand the complex dynamics of teaching and learning second/foreign languages. In this study, 18 first-year undergraduate students were engaged in a class project called e-autobiography. Naturalistic observations, participants’ autobiographical writings, and an open-ended questionnaire were used to collect the data. Analysis of the triangulated data indicated three main findings: most students constructed their identity as “users of English,” considered themselves “privileged” to have gotten the opportunity to learn English, and believed that their geographical location was crucial to their identity construction as well as success in learning English. The article concludes with a call for increased attention to learner identity, which is closely related to successful acquisition of foreign/second language(s).